Impact of Patient Follow‑Up on Weight Loss after Bariatric Surgery - Khan, Dr. Mohsin (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Context: Bariatric surgery is an effective method in inducing significant weight loss in patients suffering from obesity. Despite the strong evidence on its clinical effects, the data on its mid‑ and long‑term follow‑ups and durability are limited. This study is to evaluate the impact of bariatric surgical procedures on weight loss and resolution of comorbidities after surgery. Subjects and Methods: This was a retrospective, single‑center cohort study including 146 participants in whom laparoscopic sleeve gastrectomy, Roux‑en‑Y gastric bypass, one‑anastomosisgastric bypass, and balloon were performed between 2021 and 2024. Standardized weight loss measures were compared using an analysis of covariance. Results: The mean (standard deviation) age of patients involved in this study is 43.41 ± 12.09 years with a preoperative weight and body mass index (BMI) of 117.23 ± 23.027 and 44.93 ± 8.02, respectively. The mean follow‑up period is 2.9 years (0.83–4 years). Patients reported a mean percentage total weight loss (%TWL) of 8.1 ± 15.66%, percentage excess weight loss (%EWL) of 18.92 ± 40.56, and excess BMI loss of 18.38 ± 42.7 at the follow‑up point. The remission of diabetes was significantly improved by 17%. 0.89% of patients adhered to follow‑up visits till the end of the study. Conclusions: Bariatric surgery demonstrated a beneficial association resulting in substantial weight loss and remission of diabetes. Further large, multi‑site cohort studies on Indian population are needed to substantiate the evidence.